Avoiding Bernard: The Illustration of Insecure Attachment in Not Now, Bernard - Barbara Katharina Reschenhofer (CLELEjournal, 2023)
By means of attachment theory, Reschenhofer gains a more in-depth understanding of the verbal and pictorial complexities of Not Now, Bernard. She examines how texts like McKee’s classic can be used to promote visual literacy, emotional literacy, theory of mind and co-operative booktalk in the English language classroom.